2005
DOI: 10.1002/art.21033
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of rat adjuvant‐induced arthritis by Met‐RANTES

Abstract: Objective. CC chemokines and their receptors play a fundamental role in trafficking and activation of leukocytes at sites of inflammation, contributing to joint damage in rheumatoid arthritis. Met-RANTES, an amino-terminal-modified methionylated form of RAN-TES (CCL5), antagonizes the binding of the chemokines RANTES and macrophage inflammatory protein 1␣ (MIP-1␣; CCL3) to their receptors CCR1 and CCR5, respectively. The aim of this study was to investigate whether Met-RANTES could ameliorate adjuvantinduced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
83
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 41 publications
7
83
1
1
Order By: Relevance
“…Regulation of bone resorption by osteoclasts is essentially mediated via the RANKL/RANK/OPG system (8,9,11,24,43). We observed that celastrus/celastrol-treated rats had a decrease in serum RANKL levels along with a reduction in RANKL/OPG ratio compared with the control rats.…”
Section: Discussionmentioning
confidence: 66%
“…Regulation of bone resorption by osteoclasts is essentially mediated via the RANKL/RANK/OPG system (8,9,11,24,43). We observed that celastrus/celastrol-treated rats had a decrease in serum RANKL levels along with a reduction in RANKL/OPG ratio compared with the control rats.…”
Section: Discussionmentioning
confidence: 66%
“…EGCG was brought into suspension in PBS. EGCG (100 mg/kg) or PBS was administered i.p., with treatment initiated on day 7 after arthritis induction when the first signs of joint inflammation and pain are usually noted and continued until day 16 (46,47). On day 17, animals were anesthetized for blood collection by cardiac puncture and then killed for biochemical and cytokine analysis.…”
Section: Preparation Of the Egcg Solutionmentioning
confidence: 99%
“…Clinical parameters measured included articular index (AI) score and ankle circumference, as previously described (20). AI scores were recorded for each ankle joint by a consistent observer blinded to the treatment received by the animals.…”
Section: Clinical Measurementsmentioning
confidence: 99%
“…Therapeutic intervention before disease onset using CCR1 and CCR5 inhibitors reduces joint inflammation, bone erosion, proinflammatory cytokines, and monocyte and neutrophil recruitment in experimental arthritis (20,21). We are not aware of studies that have examined the inhibition of RANTES, initiated after the onset of clinical disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation